Floating ceilings: new horizons of design - Kapan , Айтолкын (Рroblems of engineering and professional education, 2024)
The article examines the history of the development of suspended ceilings, from their initial appearance to modern innovative technologies and materials used to create them. Suspended ceilings are one of the most interesting and innovative trends in modern interior design, which not only transform the space, but also serve as an important element of the architectural composition. These ceilings, which have become widespread thanks to the use of new lightweight materials such as polymers and fiberglass, allow you to create a weightless effect and add depth to the interior. In the historical context, suspended ceilings were used to create a sense of grandeur and luxury, while their modern use includes residential and commercial use to hide utilities, create lighting effects and acoustic properties. With the development of technologies such as suspended structures, these ceilings have become more accessible and diverse in use. The main advantages are ease of installation, the ability to create unique design solutions and improved acoustics. However, there are also a number of disadvantages, such as design limitations and possible difficulties in maintenance. Floating ceilings are not only an element of interior design, but also an important aspect of sustainable urban design, offering new ways to address congestion and utilize vertical space.